Risk-taking behaviours among out-of-school female adolescents in Ibadan North local government area, Nigeria - E., Ibiyemi Monisade; O., Ibirongbe Demilade; K., Omode Paulinus; J., Akiniyi Rotimi (International Journal Of Community Medicine And Public Health, 2025)
Background: Adolescents participate in risky behaviors that put their health at risk. The study aims at identifying risky behaviors and to determine the characteristics that influence risky behaviors among out-of-school adolescents and young females in Ibadan North Local Government Area, Nigeria. Methods: This was a cross-sectional study, involving 305 young females aged 10 to 24 chosen using a multistage random sampling technique. A self-administered questionnaire was utilized to gather quantitative data. Data was entered and analyzed using SPSS version 20, while chi-square test was used to analyze the data. Results: Respondents’ average age was 18.5±3.3 years. The majority (61.6%) have had sex, and 103 people (54.8%) did not wear a condom during their most recent sexual experience. The average age at sexual debut was 17.5±2.4 years. Of those sexually active, 76 (40.4%) had more than two sexual partners, while 123 (12.2%) have had transactional sex. Also, 54 (45.4%) consume alcohol, and 26 people (8.5%) had ever smoked. Heroin 9 (3.0%), cannabis 8 (2.6%), and cocaine 3(1.0%) were the substances commonly abused. It was shown that the respondents’ living arrangements and alcohol consumption were highly correlated (p=0.00 and 0.00). Substance abuse and engaging in sexual activity or sex for profit were significantly correlated (p=0.00 and 0.01). Conclusions: Using a multi-domain interventional approach can help to improve adolescents understanding on the harmful effect of risky behaviors and also reduce risk behaviors to avoid future health problems.